Pengaruh Peer Education terhadap Pengetahuan, Sikap, dan Niat Pencegahan Anemia Remaja Putri MAN 13 Jakarta Selatan Tahun 2025 - Muhammad Nur Zaman; Nurul Huriah Astuti (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Anemia among adolescent girls remains a significant health issue. Anemia interventions are necessary as a preventive measure; this study aims to examine the effect of health promotion using the peer education method on knowledge, attitudes, and intentions regarding anemia prevention among adolescent girls at MAN 13 South Jakarta. This study employed a quasi-experimental design using a one-group pretest-posttest approach with a sample of 49 respondents; data were collected before and after the peer education intervention. This study has been approved by the Health Research Ethics Committee (KEPK) of University of Muhammadiyah Prof. DR. HAMKA. The results showed a significant effect: the mean knowledge score before the intervention was 8.65, while after it was 9.53 (p-value <0.001); the mean attitude score before the intervention was 34.67, while after it was 36.57 (p-value <0.023); and the mean intention to prevent anemia was 31.29 before the intervention and 34.82 after, with a p-value <0.001. These findings indicate that peer education is effective in improving knowledge, attitudes, and intentions to take preventive actions against anemia among adolescent girls. Thus, peer education can serve as a strong alternative health promotion strategy for preventing anemia among adolescents.